2008
DOI: 10.1007/s00300-008-0470-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in biomass and elemental composition during early ontogeny of the Antarctic isopod crustacean Ceratoserolis trilobitoides

Abstract: Changes in biomass and elemental composition (dry mass, DM; carbon, C; hydrogen, H; nitrogen, N) were studied throughout the early ontogeny in the serolid isopod Ceratoserolis trilobitoides from a population off the South Shetland Islands (62°24.35 0 S, 61°23.77 0 W). Specimens of C. trilobitoides were sampled using an Agassiz trawl during the expedition ANT XXIII-8 of RV Polarstern in January 2007. Classification of embryos into six developmental stages followed previous studies. No clear sizedependant fecund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
(60 reference statements)
1
7
0
1
Order By: Relevance
“…Similar patterns were found in Carcinus maenas larvae suffering from starvation (Dawirs, 1986), temperature and osmotic stress (Torres et al, 2002). Here, carbon is metabolized at higher rates than nitrogen, which indicates that unfavourable conditions have comparable effects on the metabolism of larvae (Anger, 2001;Heilmayer et al, 2008). At 22°C, the generally constant overall relative carbon content and the increasing C:N ratio points to protein degradation due to high metabolism, which is also described for larvae after long periods of food deprivation (Anger, 2001) and likely the result of a mismatch of energy supply and energy demand.…”
Section: Discussionsupporting
confidence: 54%
“…Similar patterns were found in Carcinus maenas larvae suffering from starvation (Dawirs, 1986), temperature and osmotic stress (Torres et al, 2002). Here, carbon is metabolized at higher rates than nitrogen, which indicates that unfavourable conditions have comparable effects on the metabolism of larvae (Anger, 2001;Heilmayer et al, 2008). At 22°C, the generally constant overall relative carbon content and the increasing C:N ratio points to protein degradation due to high metabolism, which is also described for larvae after long periods of food deprivation (Anger, 2001) and likely the result of a mismatch of energy supply and energy demand.…”
Section: Discussionsupporting
confidence: 54%
“…The attachment habit of A. nitens and the high degree of care given by brooders would give them a selective advantage over species with planktotrophic larvae in the food-limited glacial conditions (Poulin et al 2002;Heilmayer et al 2008;Thatje et al 2005Thatje et al , 2008.…”
Section: Broodingmentioning
confidence: 99%
“…The energetic constraints set under such conditions would seem to favour the protected development (e.g. brooding) as the most efficient method of overcoming larval mortality in comparison to free development (for discussion see Heilmayer et al 2008). Increasing the proportion of reproductive effort invested into a single offspring may improve its chance of survival, but at the expense of a reduced fecundity (Vance 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Rhopiella hirsuta has been found down to the depths of 3845 m (Mah 2009), the deepest sample in this study being retrieved from 658 m. Females G and H were the only ones to be sampled from Bransfield Strait, the most southerly of the sample sites (63°04, 50′S) whereas all other females came from waters off the South Shetland Islands, suggesting a possible (albeit small) latitudinal gradient in reproductive traits, with low fecundity and large juvenile size occurring at higher latitudes, as an adaptation to surviving the cold (for discussion see Thorson 1950;Lovrich et al 2005;Heilmayer et al 2008). However, data derived from our small sample size need to be treated with caution, and a review of Thorson's work by Pearse (1994) concluded that no latitudinal or depth trend in echinoderms with brooded development was apparent.…”
Section: Female Fecundity and Brood Dynamicsmentioning
confidence: 99%
“…For the 34 species of Antarctic asteroids for which reproductive patterns are known, 19 (56% majority) produce non-pelagic larvae, almost exclusively by brooding (Pearse and Bosch 1994). Brooding is equally exemplified across a wide range of other Antarctic taxa including molluscs (Simpson 1977;Picken 1980;Hain and Arnaud 1992), and paracarideans (Heilmayer et al 2008).…”
Section: Introductionmentioning
confidence: 99%